Breaking The Barriers: Understanding The Effects Of Practical Barriers In The Way Of Female Participation In Sports At University Level - Sadia Mahreen, Dr. Noor Muhammad, Dr. Yasir Iqbal Waraich, Abdullah, Afshin Begum (Migration Letters, 2024)
This study explores the practical barriers impacting female sports participation at the university level in Khyber Pakhtunkhwa, Pakistan. Employing a cross-sectional survey research design, data were collected from 337 female athletes across 15 universities (2 private and 13 public) that participate in sports competitions. Key barriers examined include inadequate facilities, limited access to facilities, financial constraints, and time constraints. Normality tests, including Shapiro-Wilk (W = 0.950 for inadequate facilities, p = 0.023) and [1]Kolmogorov-Smirnov (D = 0.126, p = 0.042), indicated that while most variables were normally distributed, inadequate facilities did not meet normality assumptions. Consequently, non-parametric analyses were applied. The study found that inadequate facilities significantly reduce female participation in sports (p < 0.05), while financial constraints (p = 0.034) and time constraints (p = 0.041) also have a notable impact. Recommendations include enhancing sports facilities, providing financial assistance, and adjusting academic schedules to improve participation. The findings highlight the need for targeted interventions to support female athletes in higher education.